Riding on air in Virginia [Maglev train]. - Rosenblatt, A. (IEEE spectrum)
The first operational magnetic levitation system in the United States will carry students across a university campus. Other magnetically levitated trains may cover many more kilometers and run at much higher speeds, but riders of the one at Old Dominion University (Norfolk, Va.) will have someplace to go at the other end. Instead of being used for test alone, this Maglev train will be unique in actually carrying passengers. The seminal system, conceived and designed by American Maglev Technology Inc. (Atlanta), is to begin operation on 15 November 2002. It has just one vehicle, which will travel along a single, 1036-meter-long track, suspended by electromagnetic forces on a cushion of air. Its top speed is only 67 km/h, because of the short distance between stations.